2021
DOI: 10.1038/s41598-021-91783-2
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and interactions among triatomine bugs, their blood feeding sources, gut microbiota and Trypanosoma cruzi in the Sierra Nevada de Santa Marta in Colombia

Abstract: Chagas disease remains a major neglected disease in Colombia. We aimed to characterize Trypanosoma cruzi transmission networks in the Sierra Nevada de Santa Marta (SNSM) region, to shed light on disease ecology and help optimize control strategies. Triatomines were collected in rural communities and analyzed for blood feeding sources, parasite diversity and gut microbiota composition through a metagenomic and deep sequencing approach. Triatoma dimidiata predominated, followed by Rhodnius prolixus, Triatoma mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…maculata with 11 and R . prolixus with 9, sharing Homo sapiens , Canis , Felis , Bos , Sus , Didelphis , and Metachirus [ 63 ], herein identified as well ( S4 Fig ). These results imply that T .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…maculata with 11 and R . prolixus with 9, sharing Homo sapiens , Canis , Felis , Bos , Sus , Didelphis , and Metachirus [ 63 ], herein identified as well ( S4 Fig ). These results imply that T .…”
Section: Discussionmentioning
confidence: 90%
“…These results imply that T . dimidiata ’s feeding behavior is highly similar to other successful vectors, evidencing a parasite’s transmission cycle encompassing the broadest range of hosts and vectors that do not support a strict domestic/sylvatic transmission cycle [ 63 ]. This highlights the importance of T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to field standardization, longitudinal evaluations of this methodology are needed alongside parallel TMCs and community serosurveys, to quantitatively evaluate this technique, to establish the true LoD of parasite/vector eDNA in the field using both FTA cards and cotton-tipped swabs, to determine how seasonal changes in triatomine population dynamics affect eDNA degradation and to optimise timing and logistics of eDNA wall sampling. While this study only investigated presence/absence of T. cruzi and R. prolixus , further research is warranted to assess the possibility of using recovered eDNA for community-wide blood-meal analysis, surveillance of molecular insecticide resistance and characterization of parasite and vector population genetic structures, including reinfestation dynamics after insecticide spraying campaigns 13 , 17 , 67 . These aspects are pivotal to the development of effective vector control programmes in Chagas disease endemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…A difference in the microbiota composition of triatomines on a taxonomic level between infected and non-infected insects has rarely been demonstrated before [85]. However, taking into account the overall bacterial diversity, Díaz, et al [79] showed that T. cruzi-challenged insects bare a more diverse bacterial community than the control group.…”
Section: Discussionmentioning
confidence: 98%